2019
DOI: 10.1177/1460458219864730
|View full text |Cite
|
Sign up to set email alerts
|

Data work in healthcare: An Introduction

Abstract: Healthcare organizations across the globe are currently grappling to implement tools and practices to transform data from "refuse to riches," a movement propelled by mass adoption of electronic health records (EHRs), sensors, and servers that can hold an ever-expanding volume of digital data. 1 Allegedly, "By digitizing, combining and effectively using big data, healthcare organizations ranging from single-physician offices and multi-provider groups to large hospital networks and accountable care organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 46 publications
(60 reference statements)
1
47
0
7
Order By: Relevance
“…In line with this, the concept of data work has been growing in interest. Data work in healthcare outlines work, supported by data, performed by both healthcare professionals and patients [16,17]. When work is shifted from healthcare professionals, and when patients take on larger responsibilities, they also conduct work.…”
Section: Related Workmentioning
confidence: 99%
“…In line with this, the concept of data work has been growing in interest. Data work in healthcare outlines work, supported by data, performed by both healthcare professionals and patients [16,17]. When work is shifted from healthcare professionals, and when patients take on larger responsibilities, they also conduct work.…”
Section: Related Workmentioning
confidence: 99%
“…Most recently in a special issue on data work in health care (Bossen et al . 2019a) it is suggested that ‘data work [is] a substantial element of contemporary care delivery practices’ (Grisot et al . 2019), and that it is important to understand data as the outcome of human effort – not a free‐floating resource (Bossen et al .…”
Section: Introductionmentioning
confidence: 99%
“…2019), and that it is important to understand data as the outcome of human effort – not a free‐floating resource (Bossen et al . 2019a). Particular focus is directed towards the data work carried out by professionals within clinical settings (Bjørnstad and Ellingsen 2019, Bonde et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to investment in additional ICT systems, improvements in the use of health informatics also require a reorientation of healthcare organisations around the production of data (Bossen et al, 2019). While this is often overlooked, it means that there are many new occupation groups within healthcare systems that are centred on data work and that current healthcare workers will need to further develop skills in health data management (Bossen et al, 2019). This has been recognised by many groups.…”
Section: Using His and Big Data To Learn Understand And Inform Decision-makingmentioning
confidence: 99%